Порівняльний аналіз горизонтально- і вертикально-осьових вітроустановок - Корендій, Віталій (Видавництво Львівської політехніки, 2011)
Здійснена спроба проаналізувати характерні відмінності між горизонтально- і вертикально-осьовими вітроустановками, вказати на переваги і недоліки та обґрунтувати доцільність використання кожної з них для зростання енергетичної незалежності нашої країни. Nowadays in the world the amount of horizontal-axis wind-power installations (WPI), which use the effect of aerodynamic lifting load, is about 90 %, and a few thousand of companies are engaged in the batch production of them. The lag in development of verticalaxis WPI is caused by a few reasons. At first, they were invented considerably later than horizontal-axis WPI. Secondly, until quite recently it was erroneously considered that their rapidity can not exceed one module (for horizontal-axis WPI it may reach to 14 modules). The comparison of horizontal- and vertical-axial WPI, which can be found in modern literature, usually is limited by the mention about advantages of the use of vertical-axial WPI in connection with their basic property – the insensibility to the direction of the wind and, as a result, the possibility of considerable simplification of construction of the installation. However the experience of designing and exploitation of WPI shows, that this advantage is not the only parameter of comparative assessment of these types of WPI. Vertical- and horizontal-axis WPI are fundamentally different systems, many characteristics of which do not recur. Therefore we will make an attempt to analyse differences, advantages and faults of both systems after such criteria: 1) dependence of efficiency of wind-power installation on direction of the wind; 2) coefficients of the use of the wind power; 3) starting of WPI; 4) rationality of the power chart of WPI; 5) construction of blade; 6) turn of blades; 7) energy of air flow, which is taken away by the blade; 8) degree of rapidity; 9) placing of generator and booster; 10) reliability; 11) capacity; 12) rated speed of the wind; 13) ecological aspects; 14) mass characteristics. In complex variety of properties, which commonly ambivalently characterize each type of WPI, it is impossible to use simple methods of their quality assessment (easy-heavy, difficult-simple, effectiveineffective). The quantitative analysis of total complex of characteristics of WPI, on the basis of theoretical and model-experimental researches with the purpose of receipt of data about efficiency of the use of WPIof both types in the economic and meteorological conditions of concrete region, is necessary. In general, it is necessary to to emphasize that it is impossible to satisfy the necessities of all consumers of the country. Wind power as the subindustry of power engineering will become competitive only on condition of development of different directions which are able to create the state market of wind-power technique.
The сomparative analysis of horizontal- and vertical-axis wind turbines
Keywords: вітроенергетична установка; коефіцієнт використання енергії вітру; ступніь швидкохідності; система орієнтації за напрямом вітру; система повороту лопатей; теоретична межа потужності